2016
DOI: 10.5194/acp-16-6453-2016
|View full text |Cite
|
Sign up to set email alerts
|

Simulating secondary organic aerosol from missing diesel-related intermediate-volatility organic compound emissions during the Clean Air for London (ClearfLo) campaign

Abstract: Abstract. We present high-resolution (5 km × 5 km) atmospheric chemical transport model (ACTM) simulations of the impact of newly estimated traffic-related emissions on secondary organic aerosol (SOA) formation over the UK for 2012. Our simulations include additional diesel-related intermediate-volatility organic compound (IVOC) emissions derived directly from comprehensive field measurements at an urban background site in London during the 2012 Clean Air for London (ClearfLo) campaign. Our IVOC emissions are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 73 publications
2
85
0
Order By: Relevance
“…This WRF configuration is similar to that discussed in Vieno et al (2010), where it is shown to perform well in comparison with measurements. An evaluation of the WRF-EMEP4UK modelling system against measured gaseous and particulate pollutant concentrations across the UK for 2001 to 2010 is given by Lin et al (2017), while Ots et al (2016) compares WRF-EMEP4UK air quality simulations with detailed measurements of secondary organic aerosols made in London during the 2012 ClearfLo campaign.…”
Section: Regional-scale Modelling: Emep4ukmentioning
confidence: 99%
See 1 more Smart Citation
“…This WRF configuration is similar to that discussed in Vieno et al (2010), where it is shown to perform well in comparison with measurements. An evaluation of the WRF-EMEP4UK modelling system against measured gaseous and particulate pollutant concentrations across the UK for 2001 to 2010 is given by Lin et al (2017), while Ots et al (2016) compares WRF-EMEP4UK air quality simulations with detailed measurements of secondary organic aerosols made in London during the 2012 ClearfLo campaign.…”
Section: Regional-scale Modelling: Emep4ukmentioning
confidence: 99%
“…The gaseous chemical scheme used in EMEP4UK in this study is the CRI-v2-R5 mechanism (Watson et al, 2008), which has 220 species and 609 reactions. Five classes of fine and coarse particles, with differing size and deposition properties, are used in EMEP4UK along with the MARS (Model for an Aerosol Reacting System) equilibrium module for gas-aerosol partitioning of secondary inorganic aerosol (Binkowski and Shankar, 1995;Simpson et al, 2012) and a treatment of secondary organic aerosol formation using the volatility basis set approach Ots et al, 2016). Dry (including stomatal) and wet deposition of gases and particles are simulated.…”
Section: Regional-scale Modelling: Emep4ukmentioning
confidence: 99%
“…The performance of this version of the EMEP4UK model simulating a standard suite of gas-phase components and secondary inorganic aerosol PM components is reported in Ots et al (2016a) comparing with a full year of measurements in London in 2012. In brief, Ots et al (2016a) reported an NMB of −1% and r = 0.79 for ozone, an NMB of −32% and r = 0.78 for NO x , Table 1.…”
mentioning
confidence: 99%
“…In brief, Ots et al (2016a) reported an NMB of −1% and r = 0.79 for ozone, an NMB of −32% and r = 0.78 for NO x , Table 1. SNAP source sectors as specified in the emissions input to the model (CEIP, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation